Valorization of grape pomace using green technologies - Pedras, Bruno Miguel da Silva (2022)
Renewable and green resources need to be exploited to overcome the depletion and pollution problems caused by fossil resources, while fulfilling growing necessities for energy, food, and raw materials. The transition to a bio-based economy can be the solution for sustainable global development. The concept of circular bioeconomy aims to use biomass wastes and side streams efficiently in the sustainable production of high value products. Grape pomace (GP) is the by-product generated by the wine industry. GP is composed mostly of lignocellulose, also containing proteins, lipids, sugars, and phenolic compounds. These high- value compounds can be recovered and applied in food, cosmetic or pharmaceutical industries. The work presented in this thesis explores the complete valorization of GP using a cascade process, using subcritical water (SBW), for the fractionation of red wine grape pomace (RWGP) into differentiated extracts rich in phenolics, hemicellulose carbohydrates, cellulose carbohydrates, and the recovery of lignin. The phenolic-rich and hemicellulose-rich extracts were obtained using a semi-continuous reactor in a stepwise temperature program. Different temperatures were evaluated and the highest recovery yields were achieved at 100 and 190 ᵒC, respectively for phenolics and hemicellulose. The cellulose and lignin separation was achieved at 280 ᵒC, with the complete hydrolysis of cellulose and the loss of 49 % of lignin. At 250 ᵒC, 70 % was recovered and 90 % of the cellulose was hydrolyzed. The obtained hemicellulose-rich extracts were studied as a source of prebiotics and in the formation of hemicellulose-based films. The extract exhibited prebiotic activity with the lactobacilli tested, having the best performance for Lactobacillus paracasei, with a prebiotic activity score of 0.4. The hemicellulose-based films were also successfully obtained, after a process of optimization and the addition of sorbitol and glycerol, as plasticizers.Another goal of this thesis was to add value to the high amount of sugars readily available in white wine grape pomace. The yeast Rhodotorula babjevae was chosen to grow on this carbon source and produce different high-value products. R. babjevae was able to accumulate up to 23 % (w/w) of lipids with carotenoids (45 mg/100goil), and simultaneously secrete polyol esters of fatty acids (1.1 g/L in spent medium).